Pendampingan Lokakarya Penguatan Literasi pada Program Sekolah Penggerak Tahun Ketiga di Kabupaten Soppeng - Hamzah, Rahma Ashari (Universitas Methodist Indonesia, 2024)
Strengthening literacy is an activity carried out to strengthen a person's skills in understanding, recognizing, interpreting, evaluating, reflecting various types of texts and visual, auditory and digital symbols to solve problems and increase individual capacity so they can contribute to society. The aim of this literacy strengthening assistance is that all participants are able to understand literacy concepts, are able to identify literacy misconceptions, are able to design initial learning assessments to map students' literacy skills, and are able to design school strategies to strengthen students' literacy skills. The method used is participatory throughout the learning committee including the principal, school supervisor, and 2 teacher representatives from each school, consisting of 4 elementary school levels, namely SDN 118 Ujung, SDN 100 Dare Bunga-Bungae, SDN 5 Mattiropole, and SDN 238 Laempa which in Soppeng Regency which was held on Tuesday 30 January 2024 with active participation of participants. The final result of this literacy strengthening workshop activity is a product of an initial learning assessment design to map students' literacy skills and a school strategy design to strengthen students' literacy skills. Thus, mentoring this literacy strengthening workshop can have a positive impact on schools, especially at the elementary school level in the Mobilizing School Program which can support teachers and schools in implementing literacy strengthening in schools.